Scenarios, trends and differences in entrepreneurship in Southern Spain and Nothern Morocco: a gender perspective - María del Carmen Romo Parra; Josefa García Mestanza; Teresa Vera Balanza (Ehquidad, 2022)
Many political and research agendas place the entrepreneurial subject at the epicentre of economic development. Our objective was to use a gender perspective to study asymmetries in the perception of entrepreneurship in two different but close geographic areas: Northern Morocco and Southern Spain. We conducted a survey of 1233 people in Spain and Morocco. In Morocco, the participants were (a) a sample of students from the Abdelmalek Essaadi University in the Tangier-Tetouan area and (b) a sample of university graduates living in the same area. In Spain, the participants were a sample of students from the University of Malaga (Spain). We administered a questionnaire on the participants' perceptions of entrepreneurship opportunities in their setting, their own social and political attitudes toward entrepreneurship, and their self-perception of their own entrepreneurial knowledge and skills. Our results confirm and expand on the trends described in international reports and the scientific literature. They also provide new data that may be of help in meeting the challenge posed by the gender gap in business entrepreneurship.